Notes on the Accuracy of Google Earth Pro Heading Information for Archaeoastronomy and Landscape Archaeology Studies - Romain, William F (Journal of Skyscape Archaeology, 2023)
Google Earth Pro (GEP) is a powerful tool that can be used for archaeoastronomic and landscape archaeology assessments. Of potential concern, however, is the accuracy of the GEP ruler tool and, in particular, the accuracy of heading information. In the present paper the accuracy of GEP heading information is evaluated. Comparative assessments are made using GEP imagery, airport runway diagrams and ground survey data derived from total station solar observations. These analyses indicate that the accuracy of GEP heading data is largely dependent on spatial resolution of the GEP image and length of the line being measured.